From being worried about the climate crisis to reducing or quitting traveling by air : and what Tågsemester and Vi håller oss på jorden has meant for this behavior change - Tunbjer, Ninja (SLU/Dept. of Energy and Technology, 2019)
In order to transition to a society that can exist safely within the planet's biophysical limits, we need act on all levels simultaneously. This thesis focuses on how citizens can act individually and collectively to change behavior and to create acceptance and support for politics and companies to make necessary changes. Research has shown that air traveling has increased greatly in the last decades, even if a slight change can be seen in recent years. A majority of Swedes are now aware of climate change and positive to taking the train instead of flying. But there is a gap between people’s attitudes and behavior when it comes to flying. The study is based on semi-structured interviews with Swedes who have bridged this gap of awareness and behavior to reduce or quit their private flying. It looks at how this behavior change has happened and what the initiatives Tågsemester and Vi håller oss på jorden has meant for this change. A theoretical framework of strategies to overcome psychological barriers to behavior change is used to clarify and better understand what the interviewees expressed. The study suggests that when the understanding of the negative consequences of one’s flying increases, a need to change behavior is felt and can lead to the decision to reduce or stop flying. It also shows that social support of close one’s acting as role models is very helpful in this change process. They inspire and show that it is possible to change. The study also suggests that the social networks Vi håller oss på jorden and Tågsemester is very appreciated in helping to form an intention or reinforce a decision to reduce or stop flying. They are a community of support, in this often controversial behavior change, showing that there are many who care and act for the climate. They show personal stories of inspiration and experiences, making the change appear attractive and easier. The promise to not fly for a year is also helping to make the decision to stop flying easier. The study shows that the engagement in changing air traveling behavior, tend to spill over to engagement in making other areas of one’s life sustainable as well as to seeing one’s behavior change as part of a larger political engagement.